Optimization of blade profiles for the Wells turbine. (1st December 2018) - Gratton, Tim; Ghisu, Tiziano; Parks, Geoff; Cambuli, Francesco; Puddu, Pierpaolo
Abstract: A Wells turbine, when coupled with an oscillating water column, allows the generation of power from the energy in waves on the surface of the ocean. In the present work, a tabu search is used to control the process of optimising the blade profile in the Wells turbine for greater performance, by maximising the torque coefficient. A free form deformation method is used as an efficient means of manipulating the blade profile and computational fluid dynamics in OpenFOAM are used to assess each profile in both two and three dimensions. Investigations into both the flow coefficient at which the optimization is performed and the number of control variables in the free form deformation tool are performed before optimisations are done on a two-dimensional blade at the hub and tip solidities. This results in increases to the torque coefficient of 34% and 32% at the tip and hub solidities, respectively. These results are then applied to the three-dimensional turbine, giving a 14% increase in the torque coefficient. The results are assessed and an improved method of optimising the blade in two dimensions is proposed.